Advances in Design-Based Research - Svihla, Vanessa (Frontline Learning Research, 2014)
Design-based research is a core methodology of the Learning Sciences. Historically rooted as a movement away from the methods of experimental psychology, it is a means to develop “humble” theory that takes into account numerous contextual effects for understanding how and why a design supported learning. DBR involves iterative refinement of both designs for learning and theory; this process is illustrated with retrospective analysis of six DBR cycles. Calls for educational research to parallel medical research has led learning scientists to strive for more specific standards about what constitutes DBR and what makes it desirable, especially regarding robustness and rigor. A recent trend in DBR involves efforts to extend the reach through scalability. These developments potentially endanger the designerly nature of DBR by orienting focus toward generalizability, meaning researchers must be vigilant in their pursuit of understanding how and why learning occurs in complex contexts